Design and validation of a survey on motivation of teachers facing processes of sexuality education - Hakspiel Plata, María Constanza; Niño Bautista, Lucila; Velazco Rangel, Claudia Milena; Aragón Borré, Darlen; Pineda-Rodríguez, Liliana Patricia (Universidad y Salud, 2016)
Objective: To design and validate a survey using the Rasch model with the aim of identifying internal and external motivation or discouragement in teachers of basic education and media invited to training in sexuality education. Materials and methods: A quantitative cross-sectional study with non-experimental analytical empirical approach was made in order to evaluate the survey and establish quality items, reliability and validity. The survey was developed from the theory of Deci and Ryan. 155 teachers of 12 public schools from the municipalities of Piedecuesta and El Socorro from the department of Santander, Colombia participated. Results: 51 initial surveys and 104 final ones were applied. In the initial test, it was only possible to analyze the component of external motivation and a good fit, unidimensionality, good reliability and separation for items of 0.97 and 5.76 respectively were observed. In the second test the three components (internal, external and discouragement) showed Rasch fit in terms of unidimensionality, reliability of items of 0.80, 0.97 and 0.89 and separation of 2.01, 5.78 and 2.83 respectively. There were no items with differential performance by sex. Conclusions: There is a validated and reliable survey to evaluate teachers’ motivation in front of training processes for sexuality education.